Conservative surgical management of mitral insufficiency: an alternative approach - Gregori Junior,Francisco (2012)
Mitral valve insufficiency is frequently the result of elongated or ruptured chordae tendineae. Several techniques have been described for its correction. However, when there is a severe elongation or rupture of the chordae, the most widely accepted treatment option has been valve replacement. The best long-term outcomes observed in conservative surgeries led us to choose this procedure rather than the correction of mitral valve insufficiency. We described three techniques for correction of mitral prolapse due to elongated and/or ruptured chordae tendineae. In addition, we developed mold pre built bovine pericardial chords (Braile-Gregori prosthesis) for chordae replacement. Finally, since 1987, the rigid prosthetic semicircular ring (Gregori-Braile ring) has been consistently used in our centre for correction of the posterior dilation of mitral annulus preferably in its portion close to the posteromedial commissure.